LIMITS OF THE CIVIL AND COMERCIAL MATTER IN THE REGULATION ON JURISDICTION AND THE RECOGNITION AND ENFORCEMENT OF JUDGMENTS IN CIVIL AND COMMERCIAL MATTERS - Jarusevičius, Justinas (Teisė, 2016)
The Purpose of this article is to analyze the categories, established in Brussels Convention and Brussels I or Brussels Ibis regulations, which are excluded from the area of civil and commercial matter. The matters related to bankruptcy, social security and arbitration are analyzed in this article. It is sought to reveal the contents of the category of the civil and commercial matter as well as to illustrate the main novelties of the Brussels Ibis. Conclusions show that the category of the bankruptcy case is not an independent category of the European Union, but depends on the content of the insolvency regulations of the Member States. Exclusion of the bankruptcy cases is based on the interest to provide greater efficiency within the insolvency procedures. Notion of the disputes related to the social security is interpreted restrictively to the disputes related to medical care, sickness benefits, maternity allowances, invalidity benefits, old age and survivors pensions benefits for accidents at work and occupational diseases family allowances and unemployment benefits; regression claims of the social security institutions per se should not excluded from the Brussels regime. Brussels Ibis changes previously applicable rules, related to arbitration exclusion as explicitly priority is given to New York Convention as well as Brussels Ibis might not be applied to a ruling given by a court of a Member State as to whether or not an arbitration agreement is null and void, inoperative or incapable of being performed, regardless of whether the court decided on this as a principal issue or as an incidental question. EUCJ decision in Gazprom case clarifies that arbitral tribunals are not obliged to follow the principle of mutual trust and approves arbitral tribunals’ right to prohibit private parties continue litigation in the Courts of the Member States.